Does digital transformation reduce corporate financial risks? A dual perspective of internal disclosure and external supervision - Zhang, Jing; Wu, Linman; Li, Xiaoyue (Transformations In Business & Economics, 2026)
Digital technologies lead to a new wave of technological innovation and transformation. However, existing literature has not provided systematic theoretical insights into whether digital transformation can reduce corporate financial risks. To explore the relationship between digital transformation and corporate financial risks, based on resource-based theory and signaling theory, the impact of digital transformation on corporate financial risks was analyzed by using a sample of A-share listed companies in China from 2011 to 2022. Results show that from the perspectives of internal disclosure and external supervision, digital transformation mitigates financial risks primarily by increasing analyst following and enhancing information transparency. Further analysis reveals that the inhibitory effect of digital transformation on financial risks is more pronounced in non-high-tech and non-labor-intensive enterprises. The conclusions obtained from this study provide new empirical evidence on how digital transformation can mitigate corporate financial risks and offer theoretical guidance and strategic support for stakeholders to adopt location-specific digital transformation strategies based on their resource endowments and market environments. JEL classification: M14, L25, C12.